The Role of HR Technology in HR Management Transformation: Improving Organizational Efficiency and Productivity - Suwaji, Rifki; Muhammad Muliyadi; Indarwan Andhika Kusuma (Jurnal Informasi dan Teknologi, 2024)
One of the main contributions of HR technology is to enhance HR processes' efficiency through the adoption of integrated human resource management systems. With this system, organizations can reduce administrative errors, expedite decision-making, and enhance visibility into employee data. This research aims to contribute by providing a study of the latest science on the success of HR technology implementation, which relies not only on the technology itself but also on the organization's ability to change culture and work processes. In this study, a literature approach is used to gather information and data from various sources relevant to the issues at hand. The analysis conducted finds that companies need to harness the potential of HR technology to achieve higher efficiency and remain competitive in an increasingly tight global market. By utilizing sophisticated and integrated HR management systems, companies can reduce operational costs, increase productivity, and achieve sustainable competitive advantages. It's crucial for management to ensure that the use of this technology not only yields operational efficiency but also supports long-term growth and innovation. By understanding the crucial role of HR technology in enhancing productivity and managing challenges associated with its implementation, companies can fully leverage its potential to achieve their business goals. Changes in HR management in the technology era offer significant opportunities for companies to enhance efficiency, productivity, and employee experience. However, overall, the long-term implications of HR technology changes can vary depending on how companies handle these changes. Therefore, it's essential for companies to manage change wisely and proactively.